Clinical outcomes in the treatment of femoral fracture by using intramedullary femur nailing system - Mishra, Shashank; Kumar, Mohit; Kumar, Prashant; Luthra, Gaurav (International Journal of Research in Orthopaedics, 2021)
Background: Femoral fractures are frequently occurring fractures that are caused due to large force impaction. The purpose of this study was to clinically evaluate the outcomes of treating femoral fractures with the use of the intramedullary femoral nailing system. Methods: This retrospective clinical trial consists of 32 patients with femoral fracture and are treated by using an intramedullary femoral nailing system which consists of retrograde femoral nail, gamma nails, expert femoral nail, universal intramedullary cannulated femoral nails that are manufactured by Auxein medical Pvt. Ltd. Sonipat, Haryana, India. There were 32 patients from two different hospitals i.e., first hospital group consist of 15 patients (8 male and 7 female) with mean age of 32 years and the second hospital group consist of 17 patients (9 male and 8 female). The fracture categorization was done on the basis of AO Classification of fracture and physical fitness was categorized by American society of anaesthesiologists. VAS score and HHS was used as a criterion for assessing the clinical outcomes of the patients. Results: There were 32 patients to whom surgery was performed and follow up time was 1 month, 3 months, 6 months and 12 months. After the final follow up no patient in any group complaint about the complications or any hardware related problem, there were perfect bone union in every patient. Radiological outcomes also showed proper union at 6 months follow up. Conclusions: For femoral fractures, intramedullary femoral nail gives a better result with high union rate and post-operative composure.